تصنيع وتوصيف الجسيمات النانوية ألكسيد النحاس وأكسيد الفضة باستخدام مسحوق أوراق الزيتون واختبار بعض تطبيقاتها - بوشاش, قمرة; جاب الله, آية (Université of eloued جامعة الوادي, 2025)
التصنيع األخضر لجسيمات أكاسيد المعادن النانوية باستخدام النباتات يعد بديال اا دا للطرق التقليدية للتصنيع الفيزيائي االكيميائي ا صديقة للبيئة. في ، حيث يمثل مجا هذه الدراسة، تم اًل بحثياا ااسعاا اطرقا تصنيع جسيمات أكسيد النحاس(NPs-CuO (اأكسيد الفضة النانوي (NPs-O2Ag (باستخدام أاراق الزيتون الناضجة الغنية بالمركبات الفينولية االفالفونيدات المتعارف ليها باختزال اتثبيت الجسيمات النانوية مع تراكيز مختلفة من المحاليل الملحية لتحسين اإلنتاجية، حيث ا تمدنا لى تغيير كتلة ملح المعدن )،2 4 ا 6غرام( بالنسبة لO2H.CU 2)COO(3CH (ا)،0.25 0.5 ا 0.75 غرام( بالنسبة ل (3AgNO(. اتم تأكيد اًلصطناع الحيوي الناجح للجسيمات النانوية اتمييزه باستخدام طيف األشعة فوق البنفسجية االمرئية vis-UV، تحليل فورييه لألشعة تحت الحمراء (FTIR(احيود األشعة السينية (XRD (.اأيضا دراسة النشاط المضاد للمكرابات. أظهر تحليل األشعة فوق البنفسجية االمرئية (Vis-UV (بالنسبة ل(NPs-CuO (قيم امتصاص قصوى في المدى 044-300 نانومتر، االتي تعود إلى رابطة (O-Cu(، أما بالنسبة ل(NPs-O2Ag (قيم امتصاص قصوى في المدى 644-344 نانومتر اتعود إلى رابطة (O-Ag(، بينما أظهر تحليل FTIRقماما ااضحة في المدى 544-054 سم،1− تُعزى إلى اهتزازات رابطة O-Cu كما أكدت نتائج XRDتشابه ينات الجسيمات النانوية في الشكل االحجم رغم اختالف تركيزاتها. كما تمت دراسة النشاط المضاد للبكتيريا اأبدت جسيمات (NPs-O2Ag (ذات الكتلة (g0.25( اجسيمات(NPs-CuO (ذات الكتلة (g4 (أيضا نشاطا مضادا للميكرابات معتبرا ضد سالًلت بكتيرية مختلفة. الاة لى ذلك، أظهرت كل من )NPs-O2Ag (ا (NPs-CuO (نشاطا ضد فطر المبيضات البيضاء(albicans Candida The green synthesis of metal oxide nanoparticles using plants represents a promising alternative to conventional physical and chemical manufacturing methods, constituting a broad and environmentally friendly research field. In this study, copper oxide nanoparticles (CuO-NPs) and silver oxide nanoparticles (Ag2O-NPs) were synthesized using mature olive leaves rich in phenolic compounds and flavonoids, known for their role in reducing and stabilizing nanoparticles. Different concentrations of salt solutions were employed to enhance productivity, with varying metal salt masses: (2g, 4g, and 6g) for(CH3(COO)2 CU.H2Oا and (0.25g, 0.5g, and 0.75g) for AgNO3 . The successful biosynthesis of the nanoparticles was confirmed and characterized using ultraviolet- visible (UV-Vis) spectroscopy, Fourier-transform infrared spectroscopy (FTIR), and X- ray diffraction (XRD). Additionally, antimicrobial activity was investigated. UV-Vis analysis of CuO-NPs revealed maximum absorption peaks in the range of 300–400 nm, attributed to the Cu-O bond, while Ag2O-NPs exhibited peaks between 300–600 nm, corresponding to the Ag-O bond. FTIR analysis showed distinct peaks in the 450–500 cm− 1 range, assigned to Cu-O vibrational modes. XRD results confirmed the similarity in the shape and size of the nanoparticles despite varying concentrations. Antibacterial activity was assessed, with Ag2O-NPs (0.25g) and CuO-NPs (4g) demonstrating significant antimicrobial effects against different bacterial strains. Furthermore, both Ag2O-NPs and CuO-NPs exhibited activity against Candida albicans.
كيمياء تحليلية
Keywords: الكيمياء الخضراء، الجسيمات النانوية، أاراق الزيتون، أكسيد النحاس، أكسيد; Green chemistry; nanoparticles; olive leaves; copper oxide; silver oxide; antimicrobial agents.